Leadership in Nursing: Styles, Challenges, and Barriers - Kamaryati, Ni Putu; Putu Darma Suyasa, I Gede; Putu Dina Susanti, Ni Luh; Ratih Comala Dewi, Ni Made; Aries Susanti, Ni Putu; Yudi Wahyu, I Made (Babali Nursing Research, 2024)
Background: Leadership is a crucial component of nursing management, where leadership style plays a significant role in its effective implementation. Challenges and barriers in leadership execution are essential aspects that need attention. Leadership is about the ability of an individual to influence the behavior of others towards a goal. This literature review aimed to identify effective leadership styles, as ideal leadership is a key aspiration for every organization. Methods: This study was a literature review using the PICO framework to formulate article questions. The search for articles was conducted via PubMed, Google Scholar, ScienceDirect, and Wiley using the keywords "leadership in nursing" AND "challenges" AND "barriers." A total of 15 articles were selected based on inclusion criteria. Results: Several leadership styles are evident in nursing, with transformational leadership being regarded as the most effective. In practice, the primary challenge faced is communication, while the major obstacles include issues related to workplace culture and professionalism. Conclusion: Leaders with strong leadership skills positively impact nursing care management, inspiring and motivating staff while enhancing the quality of services.